Hernia and appendectomy - Croci, Fabio; Pérez Penco, Ernesto; Tarabochia, Carlos (Cirugía del Uruguay, 1986)
Incidental appendicectomy in !he course of surgical operations originated in other causes is a practice actually performed and controversial. When this operation is carried out in the course of an intervention for a right inguinal hernia repair, it is accepted by sorne authors under given conditions, namely: with a non inflamed appendix contained in the herniary bag or visible and manifest entirely through the opening practised without necessily of widening same.